Dimensions of Internet use: amount, variety, and types - Blank, G; Groselj, D (Taylor and Francis, 2014)
We examine the dimensions of Internet use based on a representative sample of the population of the UK, making three important contributions. First, we clarify theoretical dimensions of Internet use that have been conflated in prior work. We argue that the property space of Internet use has three main dimensions: amount of use, variety of different uses, and types of use. Second, the Oxford Internet Survey 2011 data set contains a comprehensive set of 48 activities ranging from email to online banking to gambling. Using the principal components analysis, we identify 10 distinctive types of Internet activities. This is the first typology of Internet uses to be based on such a comprehensive set of activities. We use regression analyses to validate the three dimensions and to identify the characteristics of the users of each type. Each type has a distinctive and different kind of user. The Internet is an extremely diverse medium. We cannot discuss ‘Internet use’ as a general phenomenon; instead, researchers must specify what kind of use they examine.